KARAKTERISTIK ASAP CAIR DARI TIGA JENIS BAMBU - Sri Komarayati; Santiyo Wibowo (Jurnal Penelitian Hasil Hutan, 2015)
Research of liquid smoke from 3 species of bamboo has been conducted by using modified drum furnace. The purpose of this studyis to determine the chemical components and other properties of liquid smoke. The results showed that the yield of liquid smoke 3 types of bamboo ranged from 5.00 to 24.00%, a pH of 2.70 to 3.36 has been standardized Japan; gravity of 0.99 to 1.03, acetic acid 31.37 - 83.59%, from 1.37 to 2.07% methanol and 0.56 to 1.24% total phenol. Acetic acid, methanol and total phenol liquid smoke test results of black bamboo has the highest value, followed by liquid smoke and spotted bamboo lowest in the liquid smoke bamboo betung.